TEMPORAL DISTRIBUTION OF ARTHROPODS IN Borreria repens DC. AND Setaria sp. WILD PLANT SPECIES IN TEA PLANTATION AREA OF WONOSARI SINGOSARI - MALANG DISTRICT - Anggun Wulandari (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2018)
The temporal distribution of Athropods, it saw from arthropod frequency visiting to Borreria repens DC and Setaria sp. in time of observation. This research was aim to understanding Arthropod temporal distribution in Borreria repens DC and Setaria sp. wild plant in tea plantation area of Wonosari Singosari – Malang disctrict. The data collection method using the